Pengaruh Kompensasi dan Kepuasan Kerja terhadap Kinerja Driver Gojek Wilayah Gresik - Ryan Maulana Ahmad; Mudji Kuswinarno (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
This study is entitled "The Effect of Compensation and Job Satisfaction on the Performance of Gojek Drivers in Gresik Region" This study aims to analyze the effect of compensation and job satisfaction on the performance of Gojek drivers in the Gresik area. It was found that job dissatisfaction can affect overall performance, so it is important to pay attention to these factors in the application-based transportation industry. The thematic analysis method and caulitative approach were used by involving 15 Gojek drivers as research samples. The results showed that compensation has a significant effect on driver performance, both from the aspect of order income and bonuses from customers. It is expected that the results of this study can provide insights and practical solutions to improve the quality and efficiency of Gojek drivers' work.